Application of regional development science and technology in Petiga Village, Tabanan - I Wayan Eka Mahendra; I Made Darsana; I Gede Nyoman Suta Waisnawa; I Made Citra Wibawa; N Putri Sumaryani (Community Empowerment, 2022)
Petiga Village is known as the center of ornamental plants in Bali Province. However, ornamental plant farmers in this village face various obstacles, one of which is production and marketing. The Government of Tabanan Regency in collaboration with the International Institute of Tourism and Business (IPB) implements a regional development science and technology application program (PIPK) in overcoming the problems. This PIPK activity involves four partner groups, namely: the Guna Sari ornamental plant farmer group, the Mekar Sari KWT institution, the Guna Sari savings and loan cooperative, and the Sekar Pasti Wangi simantri. Through persuasive and educative methods, the PIPK program seeks to overcome the problems of farmers by carrying out activities in the form of: 1) procurement of greenhouses for structuring production stock, 2) procurement of production equipment, 3) training and assistance in cash flow and finance, 4) seminars and assistance in plant and vegetable cultivation and marketing, and 5) manufacture of bio urine installations. The results of interviews showed that the people of Petiga Village, especially the four partner groups gave a positive appreciation for all activities. There is an increase in knowledge related to production and marketing processes for ornamental plant farmers. If calculated from the income of farmers, this PIPK activity was able to increase the income of the partner group by an average of 20%.